2006
DOI: 10.1523/jneurosci.1758-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton Regulation of Glycine Receptor Number at Synapses and Diffusion in the Plasma Membrane

Abstract: Lateral diffusion of neurotransmitter receptors in and out of synapses has been postulated as a core mechanism for rapid changes in receptor number at synapses during plastic processes. In this study, we have used single particle tracking to investigate how changes in glycine receptor (GlyR) lateral diffusion properties might account for changes in receptor number at synapses after disruption of the cytoskeleton in dissociated spinal cord neurons. We found that pharmacological disruption of F-actin and microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 64 publications
(87 reference statements)
10
133
1
Order By: Relevance
“…4 A). In agreement with previous results (Dahan et al, 2003;Charrier et al, 2006;Ehrensperger et al, 2007), synaptic GlyRs displayed a confined mobility (Fig. 4 B), whereas extrasynaptic receptor had the features characteristic of free Brownian diffusion (Fig.…”
Section: Changes In Glyr Diffusion In Spinal Cord Neuronssupporting
confidence: 93%
See 2 more Smart Citations
“…4 A). In agreement with previous results (Dahan et al, 2003;Charrier et al, 2006;Ehrensperger et al, 2007), synaptic GlyRs displayed a confined mobility (Fig. 4 B), whereas extrasynaptic receptor had the features characteristic of free Brownian diffusion (Fig.…”
Section: Changes In Glyr Diffusion In Spinal Cord Neuronssupporting
confidence: 93%
“…The median D values obtained for synaptic and extrasynaptic GlyRs were consistent with previous data (Charrier et al, 2006). The analysis of synaptic trajectories of GlyRs yielded comparable values of D in the presence of the various constructs (Table 1, Fig.…”
Section: Changes In Glyr Diffusion In Spinal Cord Neuronssupporting
confidence: 89%
See 1 more Smart Citation
“…Such is the case for the excitatory glutamate AMPA receptors (Allison et al, 1998) and for glycine receptors (GlyRs) (Kirsch and Betz, 1995). This control results in part from the regulation of the physical characteristics (confinement and trapping) of lateral receptor diffusion, as demonstrated for GlyRs in spinal cord neurons (Charrier et al, 2006). However, several receptors and transmembrane proteins of the postsynaptic density (PSD) purify with detergent-resistant membrane (DRM) fractions, indicating a possible association with lipid rafts.…”
Section: Introductionmentioning
confidence: 99%
“…Closer insights into the nature of the interactions of gephyrin with the cytoskeleton were derived from a recent study using single particle tracking of GlyRs to assess the eVects of a pharmacological dissolution of Wlamentous cytoskeletal elements (Charrier et al 2006). In this study both F-actin and microtubule disruption were demonstrated to increase GlyR exchanges between synaptic and extrasynaptic membranes and simultaneously decreasing receptor dwell time at synapses.…”
Section: Analysis Of Gephyrin Dewcient Micementioning
confidence: 86%